2021 IEEE 11th International Workshop on Applied Measurements for Power Systems (AMPS) 2021
DOI: 10.1109/amps50177.2021.9586028
|View full text |Cite
|
Sign up to set email alerts
|

Instrument Transformers for Power Quality Measurements: a Review of Literature and Standards

Abstract: Measurements of Power Quality (PQ) are gaining more importance due to increasing presence of switching power converters that deform the waveform of the distributed voltage further and further away from a sine wave. Especially at medium and high voltage levels, PQ measurements are carried out by means of Instrument Transformers (ITs). A recently started European metrology project, EMPIR 19NRM05 IT4PQ, aims at establishing the methods and procedures for assessing the accuracy of ITs used for PQ measurements. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In other words, the necessity to research more complex events has incrementally grown to reach a better understanding of the operation of the current network and, therefore, the signals obtained synthetically are being adapted to this phenomenon. In addition, although the most common network faults are still mostly single events, there is a clear trend towards the combination of sag (usually considered the most common disturbance [32,64,65]) with harmonics or transients. Furthermore, by carefully analyzing the data, the number of papers in which harmonics are located as signal disturbances ( 73) is slightly higher than the number of papers that include sags (71), displacing the last one to second place in most common disturbances.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the necessity to research more complex events has incrementally grown to reach a better understanding of the operation of the current network and, therefore, the signals obtained synthetically are being adapted to this phenomenon. In addition, although the most common network faults are still mostly single events, there is a clear trend towards the combination of sag (usually considered the most common disturbance [32,64,65]) with harmonics or transients. Furthermore, by carefully analyzing the data, the number of papers in which harmonics are located as signal disturbances ( 73) is slightly higher than the number of papers that include sags (71), displacing the last one to second place in most common disturbances.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, although the most common network faults are still mostly single events, there is a clear trend towards the combination of sag (usually considered the most common disturbance [32,64,65]) with harmonics or transients. Furthermore, by carefully analyzing the data, the number of papers in which harmonics are located as signal disturbances ( 73) is slightly higher than the number of papers that include sags (71), displacing the last one to second place in most common disturbances.…”
Section: Figurementioning
confidence: 99%
“…This section aims to provide a brief overview of the literature and international standards related to ITs and PQ and to identify the PQ phenomena that are relevant for ITs testing. More details on this review can be found in [ 14 ].…”
Section: Analysis Of the Literature And Standards Regarding Its And P...mentioning
confidence: 99%
“…As a starting point, based on a thorough review of the scientific literature and existing standards, the PQ phenomena to be included in this study and their relevant characteristics in terms of voltage or current behavior, in the frequency domain or the time domain, have been defined [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation